2017
DOI: 10.1002/2016ja023478
|View full text |Cite
|
Sign up to set email alerts
|

Development of intermediate‐scale structure at different altitudes within an equatorial plasma bubble: Implications for L‐band scintillations

Abstract: An important aspect of the development of intermediate‐scale length (approximately hundred meters to few kilometers) irregularities in an equatorial plasma bubble (EPB) that has not been considered in the schemes to predict the occurrence pattern of L‐band scintillations in low‐latitude regions is how these structures develop at different heights within an EPB as it rises in the postsunset equatorial ionosphere due to the growth of the Rayleigh‐Taylor instability. Irregularities at different heights over the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…For Q‐ and D‐days, we are not only interested in the occurrence EPBs but we are also keen to know the level of degradation caused to incoming radio signal by these F‐EPBs, which is closely related to the strength and spatial scales of the ESF irregularities (Bhattacharyya et al, ). Through simulation, Keskinen et al () have demonstrated that the evolution of EPBs are considerably different during Q‐ and D‐days.…”
Section: Introductionmentioning
confidence: 99%
“…For Q‐ and D‐days, we are not only interested in the occurrence EPBs but we are also keen to know the level of degradation caused to incoming radio signal by these F‐EPBs, which is closely related to the strength and spatial scales of the ESF irregularities (Bhattacharyya et al, ). Through simulation, Keskinen et al () have demonstrated that the evolution of EPBs are considerably different during Q‐ and D‐days.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical results reported in these papers were obtained by computation of the wavefield on the ground, after the signal propagated through a one‐dimensional phase screen characterized by phase variations produced by the irregularities. In the present paper, a 2‐D model of the irregularities is used to estimate n from the S 4 indices for 251‐MHz and 1.575‐GHz signals computed under all scattering conditions, by solving the equation satisfied by the fourth moment of the complex amplitude of the wave (Bhattacharyya et al, ).…”
Section: Theoretical Results For the Frequency Exponentmentioning
confidence: 99%
“…The equation satisfied by Γ 4 in the course of the signal propagating through a thick irregularity layer followed by free space to the ground receiver (Yeh & Liu, ) is solved using the split‐step method (Bhattacharyya & Yeh, ). The irregularities are characterized by either a single‐component power‐law spectrum with slope − m as given in equation of Bhattacharyya et al () or a two‐component power‐law spectrum of the form given in equation . For the particular case of m 1 = 2 and m 2 = 4, which is considered in this paper, the constant CnormalΔN=0.5emσnormalΔN20.12em()qb2q02/20.1emπ0.12emln0.12em()qb/q0.…”
Section: Theoretical Results For the Frequency Exponentmentioning
confidence: 99%
See 2 more Smart Citations